Integrating human mobility and animal movement data reveals complex space-use between humans and white-tailed deer in urban environments - Szandra A. Péter; Travis Gallo; Jennifer Mullinax; Amira Roess; Gabriela Palomo-Munoz; Taylor Anderson (Scientific Reports)
Abstract Human expansion into wildlife habitats has increased the need to understand human–wildlife interactions, necessitating interdisciplinary approaches to assess zoonotic disease transmission risks and public health impacts. This study integrated fine-grained human foot traffic data with hourly GPS data from 38 white-tailed deer (Odocoileus virginianus), a species linked to SARS-CoV-2, brucella, and chronic wasting disease, in Howard County, Maryland. We explored spatial and temporal overlap between human and deer activity over 24 months (2018–2019) across a hexagonal tessellation with metrics like hourly popularity and visit counts. Negative binomial models were fitted to the visit counts of each deer and humans per tessellation area, using landscape features as predictors. A separate deer-only model included commercial human activity as another predictor. Spatial analysis showed deer and humans sharing spaces in the study area, with results indicating deer using more populated residential areas and areas with commercial activity. Temporal analysis showed deer avoiding commercial spaces during daytime but using them in late evening and early morning. These findings highlight the complex space use between species and the importance of integrating detailed human mobility and animal movement data when managing wildlife–human conflict and zoonotic disease transmission, particularly in urban areas with a high probability of deer–human interactions.